The effect of high-dietary K+ (HK) on Kir4.1/Kir5.1 and ROMK in the distal convoluted tubule (DCT) is not affected by gender and Cl− content of the diet - Meng, Xin-Xin; Zhang, Hao; Meng, Gui-Lin; Jiang, Shao-Peng; Duan, Xin-Peng; Wang, Wen-Hui; Wang, Ming-Xiao (Frontiers in Physiology, 2022)
Inwardly-rectifying potassium channel 4.1 (Kir4.1) interacts with Kir5.1 in the basolateral membrane of the DCT to form Kir4.1/Kir5.1 heterotetramer which plays a key role in determining the expression and activity of thiazide-sensitive Na-Cl cotransport (NCC). Whereas Kir1.1 (ROMK) is expressed in the apical membrane of the late DCT (DCT2) and plays a key role in mediating epithelial Na+ channel (ENaC)-dependent K+ excretion. High dietary-K+-intake (HK) stimulates ROMK and inhibits Kir4.1/Kir5.1 in the DCT. Inhibition of Kir4.1/Kir5.1 is essential for HK-induced inhibition of NCC whereas the stimulation of ROMK is important for increasing ENaC-dependent K+ excretion during HK. We have now used the patch-clamp-technique to examine whether gender and Cl- content of K+-diet affect HK-induced inhibition of basolateral Kir4.1/Kir5.1 and HK-induced stimulation of ROMK. Single-channel-recording shows that basolateral 40 pS K+ channel (Kir4.1/Kir5.1) activity of the DCT defined by NPo was 1.34 (1% KCl, normal K, NK), 0.95 (5% KCl) and 1.03 (5% K+-citrate) in male mice while it was 1.47, 1.02 and 1.05 in female mice. The whole-cell recording shows that Kir4.1/Kir5.1-mediated-K+ current of the early-DCT (DCT1) was 1170 pA (NK), 725 pA (5% KCl) and 700 pA (5% K+-citrate) in male mice whereas it was 1125 pA, 674 pA and 700 pA in female mice. Moreover, K+-currents (IK) reversal potential of DCT (an index of membrane potential) was -63 mV (NK), -49 mV (5% KCl) and -49 mV (5% K-citrate) in the male mice whereas it was -63 mV, -50 mV and -50 mV in female mice. Finally, TPNQ-sensitive whole-cell ROMK-currents in the DCT2 /initial-connecting tubule (iCNT) were 910 pA (NK), 1520 pA (5% KCl) and 1540 pA (5% K+-citrate) in male mice whereas the ROMK-mediated K+ currents were 1005 pA, 1590 pA and 1570 pA in female mice. We conclude that the effect of HK intake on Kir4.1/Kir5.1 of the DCT and ROMK of DCT2/CNT is similar between male and female mice. Also, Cl- content in HK diets has no effect on HK-induced inhibition of Kir4.1/Kir5.1 of the DCT and HK-induced stimulation of ROMK in DCT2/CNT.